2003
DOI: 10.2307/1543229
|View full text |Cite
|
Sign up to set email alerts
|

Cascading Trophic Impacts of Reduced Biomass in the Ross Sea, Antarctica: Just the Tip of the Iceberg?

Abstract: A significant reduction in phytoplankton biomass in the Ross Sea was reported in the austral summer of 2000-2001, a possible consequence of a disruption in sea-ice retreat due to the presence of an immense iceberg, B15 (1) (Fig. 1). Our observations in McMurdo Sound suggest temporally and trophically cascading impacts of that depression in productivity. Reduced phytoplankton stocks clearly affected the pteropod Limacina helicina (Phipps, 1774) (Gastropoda: Mollusca), an abundant primary consumer in the region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
76
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(88 citation statements)
references
References 31 publications
5
76
5
Order By: Relevance
“…Previous studies of this well-known iceberg event reported dramatic effects on lower-level taxa [25,27] and on two local populations of emperor penguins [29], but the potential impact on the population of Weddell seals was unknown. Our goal was to evaluate whether this event would (i) exceed the acclimation capacity of the species and (ii) be a threat for the population at a mid-term time scale.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies of this well-known iceberg event reported dramatic effects on lower-level taxa [25,27] and on two local populations of emperor penguins [29], but the potential impact on the population of Weddell seals was unknown. Our goal was to evaluate whether this event would (i) exceed the acclimation capacity of the species and (ii) be a threat for the population at a mid-term time scale.…”
Section: Discussionmentioning
confidence: 98%
“…Clione spp. from both hemispheres are known to have high lipid content, which may help maintain a neutral buoyancy (Phleger et al, 1997) but also facilitates extended fasting periods (up to 260days) when their exclusive prey are absent (Böer et al, 2005;Böer et al, 2006;Seibel and Dierssen, 2003). Following the incubation period, wings were dissected and preserved as described above.…”
Section: Materials and Methods Animalsmentioning
confidence: 99%
“…An asterisk indicates statistical difference between the two species in the 5-HT experiment. (B)Whole-animal rates normalized to a common body mass using significant scaling relationships measured for each species (data from Seibel and Dierssen, 2003;Seibel et al, 2007). Error bars represent the range of values calculated using the standard error for the slope of the scaling relationships.…”
Section: Muscle Ultrastructurementioning
confidence: 99%
“…lived for more than 2 yr and, although small in number, these individuals may be vital for future recruitment. Strong seasonality increases the vulnerability of early life-stages of pteropods that rely on pulses of production to thrive (Bernard and Froneman, 2009;Seibel and Dierssen, 2003). An overlap of generations gives populations greater stability in temporally variable environments.…”
Section: Seasonal Distribution Of Pteropod Biomassmentioning
confidence: 99%